Building Helpful Virtual Agents Using Plan Recognition and Planning - Geib, Christopher; Weerasinghe, Janith; Matskevich, Sergey; Kantharaju, Pavan; Craenen, Bart; Petrick, Ronald (Proceedings of the AAAI Conference on Artificial Intelligence and Interactive Digital Entertainment, 2016)
This paper presents a new model of cooperative behavior based on the interaction of plan recognition and automated planning. Based on observations of the actions of an "initiator" agent, a "supporter" agent uses plan recognition to hypothesize the plans and goals of the initiator. The supporter agent then proposes and plans for a set of subgoals it will achieve to help the initiator. The approach is demonstrated in an open-source, virtual robot platform.